2013
DOI: 10.5194/bgd-10-2767-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Export of <sup>134</sup>Cs and <sup>137</sup>Cs in the Fukushima river systems at heavy rains by Typhoon Roke in September 2011

Abstract: Effects of a heavy rain event on radiocesium export were studied at stations on the Natsui River and the Same River in Fukushima Prefecture, Japan after Typhoon Roke during 21–22 September 2011, six months after the Fukushima Daiichi Nuclear Power Plant accident. Radioactivity of 134Cs and 137Cs in river waters was 0.011–0.098 Bq L−1 at normal flow conditions during July–September in 2011, but it increased to 0.85 Bq L−1 in high flow conditions by heavy rains oc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 20 publications
2
41
0
Order By: Relevance
“…Radiocesium inputs to Japanese coastal waters also occur via riverine sources and surface water runoff (Chartin et al 2013, Nagao et al 2013, Evrard et al 2015. Cs has a high affinity for particles in freshwater, and thus its transport and delivery via rivers are associated largely with high sediment loads that occur during heavy rains and flood events.…”
Section: Figurementioning
confidence: 99%
“…Radiocesium inputs to Japanese coastal waters also occur via riverine sources and surface water runoff (Chartin et al 2013, Nagao et al 2013, Evrard et al 2015. Cs has a high affinity for particles in freshwater, and thus its transport and delivery via rivers are associated largely with high sediment loads that occur during heavy rains and flood events.…”
Section: Figurementioning
confidence: 99%
“…2.12 ), possibly caused by the fl uvial input of terrestrial FNPP-derived radioactive Cs. Nagao et al ( 2013 ) reported the transport of FNPP-derived radioactive Cs from a contaminated watershed in Fukushima Prefecture to the coastal ocean area during July and December 2011; they estimated the export fl ux of 134 Cs and 137 Cs after the heavy rain event (Typhoon Roke in September 2011) as roughly 0.74-2.6 × 10 10 Bq day −1 for the rivers of Fukushima Prefecture. These values account for 30-50 % of the export of radioactive Cs for the 10 months of March 11-December 31, 2011 in these rivers (Nagao et al 2013 ).…”
Section: Cs and 137 Cs Around Japan Islandsmentioning
confidence: 99%
“…Nagao et al ( 2013 ) reported the transport of FNPP-derived radioactive Cs from a contaminated watershed in Fukushima Prefecture to the coastal ocean area during July and December 2011; they estimated the export fl ux of 134 Cs and 137 Cs after the heavy rain event (Typhoon Roke in September 2011) as roughly 0.74-2.6 × 10 10 Bq day −1 for the rivers of Fukushima Prefecture. These values account for 30-50 % of the export of radioactive Cs for the 10 months of March 11-December 31, 2011 in these rivers (Nagao et al 2013 ). In the future, secondary dispersion of FNPP-derived radioactive Cs through rivers, as considered in Nagao et al ( 2013 ), and through groundwater should be studied to understand the long-term effects of the FNPP accident in the coastal area of East Japan.…”
Section: Cs and 137 Cs Around Japan Islandsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that these rapid changes and multiple peaks are related to the release of 137 Cs from the Ukedo River. Several heavy-rain events, which were considered to be a cause of significant export flux of 137 Cs from inland to the coastal region (Nagao et al 2013), were observed in the Ukedo River Basin from September 2011 to October 2013 (e.g., Typhoon Roke, September 2011; Typhoon Man-yi, September 2013). Rapid changes and multiple peaks of the 137 Cs distribution obtained in this study were inferred to be related to pulse-input by the heavyrain events.…”
Section: Influence Of Discharge From River Basinmentioning
confidence: 99%